2020
DOI: 10.1007/s00894-019-4266-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electronic spectra of neutral and protonated forms of anticonvulsant drug lamotrigine

Abstract: After the Covid-19 pandemic and the aggressively infection control measures taken by the governments in the whole world, the need for a rapid pharmaceutical solution was more that necessary. The computer aided chemistry and molecular docking is a rapid tool to drug screening and investigation. Moreover, more metal based drugs are tested daily by research institutes for their antiviral activity. Here, we used theoretical studies on previously published biological active complex molecules of vanadium as an examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Surface charges are only visible between Vtocdea and 6M03 (−0.029 Kcal/mol), Vtocdpa and BSA (−0.162 Kcal/mol), Vtocdpa and 6M71 (−0.294 Kcal/mol), Vtocdea and BSA (0.042 Kcal/mol), and Vtocdpa and 6M03 (−0.018 Kcal/mol). The electrostatic attraction of Vtocdea and Vtocdpa is consistent with previous research [ 113 , 120 ], demonstrating that these compounds have anti-cancer potential by disrupting the charge transfer series in mitochondria. Considering the theoretical research, we believe that compounds like Vtocdea and VXn are promising candidates for in vitro and in vivo testing of the COVID-19 virus [ 121 ].…”
Section: Overview Of Docking Studies Of the Metal Complexes Against C...supporting
confidence: 91%
See 1 more Smart Citation
“…Surface charges are only visible between Vtocdea and 6M03 (−0.029 Kcal/mol), Vtocdpa and BSA (−0.162 Kcal/mol), Vtocdpa and 6M71 (−0.294 Kcal/mol), Vtocdea and BSA (0.042 Kcal/mol), and Vtocdpa and 6M03 (−0.018 Kcal/mol). The electrostatic attraction of Vtocdea and Vtocdpa is consistent with previous research [ 113 , 120 ], demonstrating that these compounds have anti-cancer potential by disrupting the charge transfer series in mitochondria. Considering the theoretical research, we believe that compounds like Vtocdea and VXn are promising candidates for in vitro and in vivo testing of the COVID-19 virus [ 121 ].…”
Section: Overview Of Docking Studies Of the Metal Complexes Against C...supporting
confidence: 91%
“…According to our findings, drug development really should be computer-aided. [ 113 ] In comparison to the parent medication, the data showed that both polar and non-polar groups within metal chelates were balanced. The metallodrug interactions here with the receptor of the viral ADP-ribose-1 monophosphatase enzyme are promoted by this structural equilibrium.…”
Section: Overview Of Docking Studies Of the Metal Complexes Against C...mentioning
confidence: 99%
“…Molecular docking method is one of the frequently referred structure-based design methods [28,29]. We decided that because the ligand molecules would be screened as a drug candidate for Covid-19, to perform studies with several related proteins to Covid-19 as we discussed in introduction, and at least with one plasma transport protein.…”
Section: Molecular Dockingmentioning
confidence: 99%